CONCEPTUAL PRINCIPLES OF IMPLEMENTATION OF THE ORGANIZATIONAL AND TECHNICAL MODEL OF CYBER DEFENSE OF UKRAINE - Potii, Oleksandr; Semenchenko , Andriy; Dubov , Dmytro; Bakalynsky, Oleksandr; Myalkovsky , Danylo (Ukrainian Information Security Research Journal, 2023)
The conceptual bases of introduction of organizational - technical model of cybersecurity are offered in the article. In particular, its mission, purpose, purpose and goals are defined. For the first time, the forces and means of cyber defense have been identified. The architecture of organizational and technical model of cybersecurity is considered, which is a structured system consisting of three cybersecurity infrastructures, namely: organizational and management infrastructure of cybersecurity, as a set of cybersecurity entities that form and / or implement state policy in the field of cybersecurity; cyber security technological infrastructure, as a set of cyber security forces and means, as well as infrastructure that ensures the functioning of cyber security forces, information and communication networks and their resources used in the interests of cyber defense forces and basic cyber security infrastructure, as a set of critical information infrastructure, critical assets, communication and technological systems of enterprises, institutions and organizations related to critical infrastructure, as well as business entities, citizens of Ukraine and associations of citizens, other persons who carry out activities and / or provide services, related to national information resources, electronic information services, electronic transactions, electronic communications, information protection and cyber security. Thus, the implementation of the organizational and technical model of cyber defense is aimed at rapid (crisis) response to cyber attacks and cyber incidents, the introduction of countermeasures and minimizing the vulnerability of communication systems.